LAPAROSCOPIC CHOLECYSTECTOMY FOR LEFT SIDED GALL BLADDER: AN UNUSUAL CASE - Masood, Rehan; ullah, Sami; Chaudhary, Ishtiaq Ahmed; Taimur, Taimur (Journal of Ayub Medical College Abbottabad, 2009)
We report a rare case of a female patient with situs inversus totalis. She developed cholelithiasis which was diagnosed on abdominal ultrasound and she underwent laparoscopic cholecystectomy for the left sided gall bladder. The literature on this subject is reviewed. We want to highlight the important aspects of the management in such rare scenario. Keywords: Laparoscopic, Cholecystectomy, Situs inversus